The Positivity Rate of IA-2A and ZnT8A in the Chinese Han Population With Type 1 Diabetes Mellitus: Association With rs1143627 and rs1143643 Polymorphisms in the IL1B Gene - Li, Jiaqi; Sun, Xiaoxiao; Luo, Shuoming; Lin, Jian; Xiao, Yang; Yu, Haibo; Huang, Gan; Li, Xia; Xie, Zhiguo; Zhou, Zhiguang (Frontiers in Pharmacology, 2021)
[Objective] To investigate the association between the susceptibility to type 1 diabetes mellitus (T1DM) and the polymorphisms (rs1143627 and rs1143643) of interleukin1beta (IL1B) genes in the Chinese Han population. [Methods] MSD method was used to detect the concentration of IL-1 β including 24 T1DM patients and 27 healthy controls. MassARRAY was used to analyze the polymorphisms of IL1B gene in 510 classical T1DM patients and 531 healthy controls. The general data of T1DM patients and healthy controls were compared by Chi-square test and Mann-Whitney U test. Chi-square test and logistic regression were used to analyze the frequency distribution of alleles and genotypes of polymorphisms in IL1B gene. Kruskal-Wallis H test and chi-square test were chosen to perform the genotype-phenotype analysis of rs1143627 and rs1143643 in IL1B gene. [Results] ① The concentration of IL-1 β in T1DM patients was significantly higher compared to the healthy controls. ② rs1143627 and rs1143643 in IL1B gene were significantly correlated with the positive rate of IA-2A and ZnT8A, rs1143627 with genotype GG and rs1143643 with genotype CC in the case group showed lower positive rates of IA-2A and ZnT8A. ③ There was no significant difference in genotypes of rs1143627 (GG/GA/AA) and rs1143643 (CC/CT/TT) between the case group and the control group (P>0 .05), as well as their allele frequencies between two groups. ④ rs1143627 and rs1143643 are not linked to the T1DM susceptibility under different genetic models. [Conclusion] rs1143627 and rs1143643 in IL1B gene correlate with the positive rate of IA-2A and ZnT8A in the Chinese Han population with T1DM.